2011
DOI: 10.1128/jvi.01984-10
|View full text |Cite
|
Sign up to set email alerts
|

ALIX/AIP1 Is Required for NP Incorporation into Mopeia Virus Z-Induced Virus-Like Particles

Abstract: During virus particle assembly, the arenavirus nucleoprotein (NP) associates with the viral genome to form nucleocapsids, which ultimately become incorporated into new virions at the cell membrane. Virion release is facilitated by the viral matrix Z protein through its interaction with the cellular endosomal sorting complex required for transport (ESCRT) machinery. However, the mechanism of nucleocapsid incorporation into virions is not well understood. Here, we demonstrate that ALIX/AIP1, an ESCRT-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
43
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 49 publications
7
43
0
1
Order By: Relevance
“…Recent studies showed that mutation of Y57 in TCRV Z almost completely blocked the incorporation of N protein into Z-directed VLPs, though it had no effect on Z budding activity (18,50). Similar results were observed for Mopeia virus Z protein, whose YLCL sequence was also shown to be needed for its interaction with a cellular protein (AIP1) of the multivesicular body pathway (45). In light of our findings demonstrating that TCRV Z residues Y57 and L58 are important for L binding (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Recent studies showed that mutation of Y57 in TCRV Z almost completely blocked the incorporation of N protein into Z-directed VLPs, though it had no effect on Z budding activity (18,50). Similar results were observed for Mopeia virus Z protein, whose YLCL sequence was also shown to be needed for its interaction with a cellular protein (AIP1) of the multivesicular body pathway (45). In light of our findings demonstrating that TCRV Z residues Y57 and L58 are important for L binding (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, the Z protein plays an essential role in virion assembly and budding, sharing several characteristics with other negative-strand RNA virus matrix proteins. Expression of Z protein in mammalian cells, in the absence of other viral proteins, leads to the assembly and budding of virus-like particles (VLPs) (8,36,45,46,50). Furthermore, the Z protein C-terminal region contains prolinerich late domains (PTAP and/or PPPY), which are important for the recruitment of host proteins that assist in the late stages of budding (36,49).…”
mentioning
confidence: 99%
“…Thus, RNA-free NP seems to exist exclusively as a trimer, which presumably has biological relevance. Besides being the building block of ribonucleoproteins, NP has additional functions during the life cycle of the virus, such as interaction with L and Z proteins and cellular proteins, budding of particles, suppression of the interferon response, exoribonuclease activity, and nucleotide binding (15)(16)(17)(18)(19)(20)(21)(22)(23). Some of these or other so far unknown functions of NP might be associated specifically with the trimeric configuration.…”
Section: Discussionmentioning
confidence: 99%
“…It physically associates with itself as well as with L and Z proteins (15)(16)(17)(18). The association with Z protein and ALIX/AIP1, an ESCRT-associated host protein, is important for incorporation of NP into virus-like particles (15,(17)(18)(19). In addition, NP acts as an interferon antagonist (20,21).…”
mentioning
confidence: 99%
“…Z has been implicated in many facets of the arenavirus replication cycle and is the primary driving force of virion maturation (13). In addition to recruiting the cellular endosomal sorting complex required for transport (ESCRT) machinery to mediate virion budding (13,14), Z has been demonstrated to interact with the translation initiation factor eIF4E (15) as well as retinoic acid inducible gene I (RIG-I), promyelocytic leukemia protein (PML), and proline-rich homeodomain protein (PRH) (16)(17)(18). Thus, Z is positioned at the center of a network of host and viral connections and may serve as a crucial viral sensor of the host cellular environment.…”
mentioning
confidence: 99%